Priorities, Narratives, and Collaboration: Insights From Evolving Federal Mandates on Food Systems in Canada - Wilkes, Johanna; Perttula, Claire (Frontiers in Communication, 2022)
Whether it is in a post-election period, a cabinet shuffle, or prorogation of parliament, the speech from the throne and mandate letters signal a government's priorities as they relate to emergent issues and long-standing public policy challenges. While the speech from the throne has been regularly available through parliamentary and government records, federal mandate letters have only been made publicly available more recently, and little research has been done on their role in shaping change. Using Critical Discourse Analysis (CDA), the authors explore how the overarching narratives presented by the current federal government have evolved across the period from 2015 - 2021. The authors then compare these narratives with the mandated commitments to the Minister of Agriculture and Agri-Food Canada (AAFC) during the same period. Through this comparative analysis, the authors highlight how the overarching narratives that emerged in later mandates, in particular the need to address systemic inequity, diverge with the commitments delivered to the Minister of AAFC. Part of the reason for identifying the divergence between central narratives and the current AAFC mandate is the hope that better alignment is possible. This includes making a new food policy environment in Canada; One that is equitable, prosperous for all, supports true reconciliation and Indigenous sovereignty, and ushers in a brighter future for the next generation and our planet. To conclude, the authors present alternative food systems frameworks that could help better achieve the more just and resilient world that the federal government narratives outlines.